Ferroptosis-related gene expression in the pathogenesis of preeclampsia - Ding, Yuzhen; Yang, Xiaofeng; Han, Xiaoxue; Shi, Meiting; Sun, Lu; Liu, Mengyuan; Zhang, Ping; Huang, Zhengrui; Yang, Xiuli; Li, Ruiman (Frontiers in Genetics, 2022)
Background: Preeclampsia (PE) is one of the leading causes of maternal and fetal morbidity and mortality worldwide. Placental oxidative stress has been identified as a major pathway to the development of PE. Ferroptosis is a new form of regulated cell death that is associated with iron metabolism and oxidative stress, and likely mediates PE pathogenesis. The aim of the study was to identify the key molecules involved in ferroptosis to further explore the mechanism of ferroptosis in PE. Methods: Gene expression data and clinical information were downloaded from the GEO database. The limma R package was used to screen differentially expressed genes (DEGs) and intersected with ferroptosis genes. The GO and KEGG pathways were then analyzed. Next, hub genes were identified via weighted gene co-expression network analysis (WGCNA). Receiver operating curves (ROCs) were performed for diagnostic and Pearson’s correlation of hub genes and clinicopathological characteristics. Immunohistochemistry and Western blot analysis were used to verify the expression of hub genes. Results: A total of 3,142 DEGs were identified and 30 ferroptosis-related DEGs were obtained. In addition, ferroptosis-related pathways were enriched by GO and KEGG using DEGs. Two critical modules and six hub genes that were highly related to diagnosis of PE were identified through WGCNA. The analysis of the clinicopathological features showed that NQO1 and SRXN1 were closely correlated with PE characteristics and diagnosis. Finally, Western blot and immunohistochemistry analysis confirmed that the expression of the SRXN1 protein in the placental tissue of patients with PE was significantly elevated, while the expression of NQO1 was significantly decreased. Conclusions: SRXN1 and NQO1 may be key ferroptosis-related proteins in the pathogenesis of PE. The study may provide a theoretical and experimental basis for revealing the pathogenesis of PE and improving the diagnosis of PE.